6x-2-5x=11

Simple and best practice solution for 6x-2-5x=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2-5x=11 equation:


Simplifying
6x + -2 + -5x = 11

Reorder the terms:
-2 + 6x + -5x = 11

Combine like terms: 6x + -5x = 1x
-2 + 1x = 11

Solving
-2 + 1x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 1x = 11 + 2

Combine like terms: -2 + 2 = 0
0 + 1x = 11 + 2
1x = 11 + 2

Combine like terms: 11 + 2 = 13
1x = 13

Divide each side by '1'.
x = 13

Simplifying
x = 13

See similar equations:

| 7x(-x+6)= | | 11=6x-2-5x | | y+8=2y+4 | | 3x+5=-4x | | 0.5(-8p+1)=4p+1 | | 5+3n=40-4n | | 7x+2x=8x+16 | | -8(.2x+.4)-1.7=-.1 | | 5t-6=t^2 | | 10-4*3=3+13 | | 5x^2+6x=9 | | 10-4*4=4+13 | | 10-4*8=8+13 | | 20+.15x=50 | | 30+.10x=50 | | 30+.10x=20+.15x | | 7x+5=-7+3x+20 | | 6x+34+8x=14 | | 9a^2=30+39a | | 60=lwh | | 0=320x-x^2 | | 4600-(100+3x)=0 | | 7+4(3x-5)=9-3(2x+1) | | W=4w | | 2000=225(x+3.5) | | 7-4(3x-5)=9-3(2x+1) | | 0=675x-16250-x^2 | | 9x^2+48x+140=0 | | 2x^2-13x+4.25=0 | | 360=2lw+2lh+2wh | | 7+4(3x-5)=9-3(2x-1) | | 3+2x=7x-47 |

Equations solver categories